Yafet-Kittel-type magnetic order in Zn-substituted cobalt ferrite nanoparticles with uniaxial anisotropy - Topkaya, R.; Baykal, A.; Demir, A. (Springer, 2013)
Zn-substituted cobalt ferrite (ZnxCo1-xFe2O4 with 0.0 <= x <= 1.0) nanoparticles coated with triethylene glycol (TREG) were prepared by the hydrothermal technique. The effect of Zn substitution on temperature-dependent magnetic properties of the TREG-coated ZnxCo1-xFe2O4 nanoparticles has been investigated in the temperature range of 10-400 K and in magnetic fields up to 9 T. The structural, morphological, and magnetic properties of TREG-coated ZnxCo1-xFe2O4 NPs were examined using X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectra, transmission electron microscopy (TEM), and vibrating sample magnetometry (VSM). The average crystallite size estimated from X-ray line profile fitting was found to be in the range of 7.0-10 nm. The lattice constant determined using the Nelson-Riley extrapolation method continuously increases with the increase in Zn2+ content, obeying Vegard's law. TEM analysis revealed that the synthesized particles were nearly monodisperse, roughly spherical shaped nanoparticles in the size range of 9.0-15 nm. FT-IR spectra confirm that TREG is successfully coated on the surface of nanoparticles (NPs). The substitution of non-magnetic Zn2+ ions for magnetic Co2+ ions substantially changes the magnetic properties of the TREG-coated ZnxCo1-xFe2O4 NPs. The saturation magnetization and the experimental magnetic moment are observed to initially increase (up to x = 0.2), which is explained by Neel's collinear two-sublattice model, and then continuously decrease with further increase in Zn content x. This decrease obeys the three-sublattice model suggested by Yafet-Kittel (Y-K). While the Y-K angle is zero for the CoFe2O4 NPs coated with TREG, it increases gradually with increasing Zn concentrations and extrapolates to 82.36 degrees for ZnFe2O4 NPs coated with TREG. The increase in spin canting angles (Y-K angles) suggests the existence of triangular (or canted) spin arrangements in all the samples (except for the samples with x = 0.0) under consideration in this work. From the computation of Y-K angles for the TREG-coated ZnxCo1-xFe2O4 NPs, it can be concluded that all the zinc-doped cobalt ferrite nanoparticles (for x > 0.0) have a Y-K-type magnetic order, while the pure cobalt ferrite nanoparticles (x = 0.0) have a Neel-type magnetic order. Zero field cooled (ZFC) and field cooled (FC) measurement results further verify that the samples with 0.6 <= x <= 1.0 have superparamagnetic behavior at room temperature, which shows weak interaction between magnetic particles. The blocking temperatures obtained from ZFC-FC curves decrease as a function of Zn concentration. It was found that the effective magnetic anisotropy, the coercivity, and remanence magnetization continuously decrease with increasing Zn concentration. Lower reduced remanent magnetization (M-r/M-s) values (<0.5) suggest that all the samples have uniaxial anisotropy. Ferromagnetic resonance (FMR) measurement shows that the FMR spectra of all the samples have broad linewidth because of the magnetic nanoparticles with randomly distributed anisotropy axes, and the decrease in the internal field conversely leads to the increase in the resonance field with respect to increasing Zn concentration.
Keywords: Magnetic nanoparticles; Ferromagnetic resonance; Yafet-Kittel angle; Magnetic anisotropy